Mapping of landslide susceptibility using analytical hierarchy process on the example of the right bank of the Kaniv Reservoir - Orlenko, Tetiana; Sedlerova, Olga; Lybskyi, Mykola; Golubov, Stanislav; Khyzhniak, Anna (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2023)
The study of landslide-prone areas requires the analysis of a large amount of objective data, products of remote sensing data processing (spatial images, digital terrain elevation data and analytical data on calculated indices), analytical maps based on field measurements. All these data make it possible to objectively and more accurately characterize the studied territory. It is important, based on the results of the assessment, to get a conclusion about favorable, unfavorable and dangerous areas. The result is a landslide susceptibility map. In this study, we carried out the procedure of creating a landslide susceptibility map at the regional level for the Rzhyshchiv united territorial community of the Kyiv region. Nine factors that influence the development of landslides or become indicators of landslide processes are selected. A description of the algorithm for creating a landslide susceptibility map using the method of hierarchical analysis is provided. The obtained result gives an idea of the different propensity of the areas of the studied territory to the development of landslide processes, it means the areas of the greatest threats, which contributes to the rational adoption of management decisions.